Learning and Pragmatic Values: Students' Positive Politeness Strategies in English Learning - Yeli Zastika (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This study aims to identify and explain the patterns and strategies of students' positive politeness in the English learning process. The research data is the utterances of 11 elementary school students who participated in private English courses in August-November 2020. The research is descriptive qualitative. Data were collected using the listening method involving conversation and recording techniques. The data collected in the tape recorder is then transcribed into a transcript of the conversation, which is the final data. Data analysis was carried out by referring to the qualitative analysis stages of Miles and Huberman (2014), which consisted of data collection, data reduction, data display, and conclusion drawing. The identification of politeness strategies is carried out by referring to Brown and Levinson's (1987) theory of positive politeness strategies. The results showed that there were seven strategies of positive politeness used by students in the learning process: exaggerate (16 utterances), intensify (23 utterances), presuppose common ground (28 utterances), joke (21 utterances), assert S 'knowledge and concern for H's want (42 utterances), offer and promise (33 utterances), optimistic (29 utterances). This study proves that learning English can collaborate with the internalization of pragmatic values in the form of language politeness. Students are not only given learning material but also linguistic values that can build a positive character for themselves in communicating.